The Socio-scientific Issues in PjBL: Impact on Digital Literacy of Senior High School Students - Purwianingsih, Widi; Olsiara, Lairani; Sriyati, Siti (Jurnal Inovasi Pendidikan IPA, 2025)
Digital literacy can be provided by the implementation of the project-based learning (PjBL) model in the learning process. This research aims to obtain information regarding the effect of socio-scientific issues (SSI)-integrated PjBL on high school students' digital literacy, especially on Circulatory System material. The method used is a pre-experiment with a one-group pre-test-post-test research design. The research subjects are 35 grade XI students of one of the senior high schools in Bandung. Data on students' scientific literacy abilities were collected by using a digital literacy questionnaire containing statements based on six digital literacy indicators, namely communication and collaboration, critical thinking, data literacy, ICT familiarity, device security, and personal security. Processing and analysis of research data uses the Wilcoxon test. The research results show the implementation of SSI-integrated PjBL by creating projects in the form of popular articles can increase students' digital literacy as indicated by an increase in the average percentage of pre-test and post-test scores from 78.45% to 88.66%. The increase in the average percentage of pre-test and post-test scores based on the N-Gain calculation results is in the medium category with an N-Gain score of 0.5069. The implementation of SSI-integrated PjBL can increase the average percentage score for each digital literacy indicator with the highest average score increase obtained by the ICT familiarity indicator. Therefore, it is concluded that the implementation of SSI-integrated PjBL has an effect on digital literacy and can be used as an alternative learning model that can encourage the improvement of students' digital literacy